Auger electron and photoabsorption spectra of glycine in the vicinity of the oxygen K-edge measured with an X-FEL. (8th October 2015) - Sanchez-Gonzalez, A; Barillot, T R; Squibb, R J; Kolorenč, P; Agaker, M; Averbukh, V; Bearpark, M J; Bostedt, C; Bozek, J D; Bruce, S; Montero, S Carron; Coffee, R N; et al.
Abstract: We report the first measurement of the near oxygen K-edge auger spectrum of the glycine molecule. Our work employed an x-ray free electron laser as the photon source operated with input photon energies tunable between 527 and 547 eV. Complete electron spectra were recorded at each photon energy in the tuning range, revealing resonant and non-resonant auger structures. Finally ab initio theoretical predictions are compared with the measured above the edge auger spectrum and an assignment of auger decay channels is performed.